Interpersonal Relationships and Subjective Well-being among Older Adults in Sheltered Housing - DaniÃ«l Johannes Herbers; Louise Meijering (Research on Ageing and Social Policy, 2015)
The aim of this article is to examine how experiences with interpersonal relationships contribute to older adults’ well-being in the residential context of sheltered housing. We draw on data collected from sixteen in-depth interviews with older adults living in sheltered housing in a small town in northern Netherlands. Our participants experienced the interaction with their children as of primary importance among their interpersonal relationships, while interactions with other residents were rather superficial. Their children offered emotional support as well as instrumental support and were found to play essential roles in our participants’ wellbeing. Moreover, participants expressed that the social and physical activities organized by the residential care-facility offered them the opportunity to remain physically and mentally active. The help received from housekeepers and caregivers was found to be another important element of interpersonal relationships and so was the reciprocal nature of support exchanged with other sheltered housing residents. We conclude that the benefits of interpersonal relationships in sheltered housing should be considered when designing policy for the well-being of older adults ageing in place.